Correlates of Compensation Polices and Employee Retainment (Bulletin of the Far Eastern Federal University. Economics and Management, 2023)
Retention is one of the key fundamentals that are necessary for organizational success. In a globalized environment, retention and engagement of high prospective employees are a huge challenge to International corporations. In many cases, even engaged employees are sometimes dissatisfied with the outcomes of organizational performance which may lead them to look elsewhere. Due to these reasons, this paper investigates compensation factors and policies that influence employee retention and examines their impacts on both International Corporations and employees. For the purpose of this study primary data was used. The ex-post facto method was employed. The population consists of the members of staff of Guinness International PLC Plant, Lagos Nigeria. Yamane formula was adopted to determine the sample size. The data was analyzed using manual and electronic based methods through the data preparation grid and statistical package for the social sciences (SPSS). Linear regression analysis method which also makes use of ANOVA was employed to test the hypothesis. The study found out that salary in compensation policy have effect on employee job security and also allowance affect job satisfaction Thus, the study recommends that International Corporations should identify those benefits which have more influence on employee retention. Furthermore, International Corporations need to revisit their present benefits package to identify those benefits which are not useful in order to replace them.